Visualization study of co-existing boiling and condensation heat transfer in a confined flat thermosyphon - Qin, Siyu (2024)
Flat thermosyphon (FTS) has gained wide attention in solving heat dissipation problems of data centers. The miniaturization of densely packed electronics has led to a demand for compact heat sinks. In this paper, a confined FTS consisting of an evaporator, condenser and customized quartz-glass chamber was developed. Bubble behaviors were investigated by the visualization approach under vacuum conditions. Effects of the space height, nominal heating power, and liquid filling ratio on the thermal characteristics were involved. Experimental results found that the bubble behaviors with 10 mm height are different from others. For 10 mm height, bubble contacts the condensation surface and then bounces back to the evaporator. The quantitative analysis shows that the boiling heat transfer coefficient with 10 mm height is 65.5 % of that with 25 mm height, and a condensation heat transfer coefficient with 10 mm height is 58.9 % of that with 20 mm height. Increasing heating power deteriorates the condensation heat transfer via forming a bubble film on the condensation surface. A small filling ratio (30 %) with 10 mm height is beneficial for the phase change heat transfer. It is hoped that these results can offer guidance for designing effective cooling devices.